DEWI IZANAMI DAN DEWA IZANAGI DALAM AGAMA SHINTO JEPANG (STUDI SEMIOTIK DALAM FILM NORAGAMI ARAGOTO) - Muflikhatun Afrianti (UIN Sunan Kalijaga Yogyakarta, 2018)
This study examines the mythology of Izanami Goddess and Izanagi God in Japanese Shinto religion and representations of Izanami Goddess and Izanagi God in the film Noragami Aragoto Adachitoka’s creation directed by Kotaro Tamura. This study is important because the story of Izanami Goddess and Izanagi God has never been adopted in modern scientific literature even though it has been listed in several anime in Japan. The research data was collected through documentation on the Kojiki and Nihonsoki books as well as capturing scenes of Noragami Aragoto films. Then analyzed using Christian Metz's language cinematography theory and Rudolf Otto's sacred theory. The results showed that firstly, based on the phenomenological perspective and sacrity from Rudolf Otto, Izanami Goddess and Izanagi God in Japanese Shinto mythology were the ancestors of the Mother and Father of the Gods and divine beings and played an active role in the creation of islands in Japan along with its contents. Secondly, in the Noragami Aragoto film, the perspective of cinematographic language Christian Metz, Izanami Goddess and Izanagi God are represented as mysteries of Father and Mother of Ebisu God (Hiruko) and Yaboku God (Awashima or Aha) with backgrounds that are very different from each other.Key Words: mythology, Shinto, Izanami, Izanagi, cinematographic language, and sacred.